2014
DOI: 10.4067/s0718-58392014000200017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different day and night nutrient solution concentrations on growth, photosynthesis, and leaf NO3- content of aeroponically grown lettuce

Abstract: Nitrate content in leafy green vegetables has raised concerns among consumers and policy makers worldwide. Several cultural practices have been evaluated to manipulate NO3 -content in fresh leaves with varying degrees of success. The present study was conducted to evaluate different concentrations of the nutrient solution applied during the day (D) and night (N) to aeroponically grown lettuce (Lactuca sativa L.) in Davis, California, USA, in the spring of 2012 with the objective of assessing the effect on grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
2
10
1
Order By: Relevance
“…But our results are slightly high compared with others studies. In relation to dry matter (DM) our means were higher than those obtained by Albornozet al [6]. …”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…But our results are slightly high compared with others studies. In relation to dry matter (DM) our means were higher than those obtained by Albornozet al [6]. …”
Section: Resultscontrasting
confidence: 84%
“…Various articles show that high level of nitrate accumulation in leaves is harmful to human health [4, 6]. Overall in our experiment, the higher rate of NO 3 − accumulation in leaves was found in all of the M 3 treatments.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…CO 2 uptake is negatively affected by stomatal closure [29]. The photosynthesis rate of some plant species is decreased by stomatal closure due to the influence of salinity [8,28,30].…”
Section: Leaf Gas Exchange Parametersmentioning
confidence: 99%
“…The leaf photosynthesis rate, stomatal conductance, leaf transpiration, and intercellular CO 2 concentration of some plants have also been seen to be significantly decreased by a higher EC of the NS in a hydroponic culture system, such as pak choi [8], lettuce [30], and papaya [16]. Coinciding with these former studies, our results also showed that leaf gas exchange parameters (P n , C i , g s , and T r ) were significantly decreased at a high EC of 8.0 dS•m −1 because the salinity stress was increased with an increasing EC of the NS.…”
Section: Leaf Gas Exchange Parametersmentioning
confidence: 99%